Comparison of Anterior Chamber Depth Measurements from the Galilei Dual Scheimpflug Analyzer with IOLMaster - Roma P. Patel; Rahul T. Pandit (Journal of Ophthalmology)
Purpose. To compare anterior chamber depth (ACD), representing the distance between the anterior corneal surface and anterior lens surface measurements between the Galilei Dual Scheimpflug Analyzer and the IOLMaster. Methods. A retrospective review of 65 individual patient eyes with normal anterior segments, and no prior ocular surgery was performed. Patients underwent ACD measurements with both devices during the same session by a trained examiner. Interdevice agreement was evaluated using paired two-tailed t-tests, Pearson correlation coefficient, and Bland-Altman analysis. Results. The mean ± standard deviation (SD) ACD for the Galilei and IOLMaster was 3.37 ± 0.36 mm (range from 2.62 to 4.13) and 3.25 ± 0.38 mm (range from 2.34 to 3.92), respectively (Pearson correlation coefficient = 0.96). ACD mean difference was 0.12 mm (P < 0.0001); 95% limits of agreement was from −0.09 to 0.34. The Galilei measured slightly longer ACD values than the IOLMaster. There was no relationship between axial length and interdevice difference. Conclusion. ACD measurements correlate well between the Galilei and IOLMaster, with Galilei values on average 0.12 mm longer than the IOLMaster.